Simple method for evaluating achievement degree of lung dose optimization in individual patients with locally advanced non‐small cell lung cancer treated with intensity modulated radiotherapy. Issue 20 (31st August 2022) - Abe, Takanori; Iino, Misaki; Saito, Satoshi; Aoshika, Tomomi; Ryuno, Yasuhiro; Ohta, Tomohiro; Igari, Mitsunobu; Hirai, Ryuta; Kumazaki, Yu; Miura, Yu; Kaira, Kyoichi; Kagamu, Hiroshi; et al.
Abstract: Background: In this study, we developed a simple method for evaluating achievement degree of lung dose optimization in individual patients with locally advanced non‐small cell lung cancer (NSCLC) treated with intensity modulated radiotherapy (IMRT). Methods: Data of 28 patients with stage IIB to IIIC NSCLC were retrospectively analyzed. All patients were treated with IMRT and a simulated three‐dimensional conformal radiotherapy (3D‐CRT) plan created for them. Dose‐volume parameters of lung were analyzed for their correlation with radiation pneumonitis (RP). Results: Over a median follow‐up of 14 months, grade 1 pneumonitis was diagnosed in 14 patients (50%), grade 2 pneumonitis in 11 (39%), and grade 3 pneumonitis in one (4%). Two patients did not develop pneumonitis. None of the patients developed grade 4 or 5 pneumonitis. Regarding dose‐volume parameter ratios between IMRT and simulated 3D‐CRT, receiver operating characteristic analysis showed that mean lung dose (MLD)IMRT /MLD3D‐CRT had the largest area under curve (0.750). Cumulative 6‐month incidences of grade 2 or greater RP were 78.4% versus 19.5% (MLDIMRT /MLD3D‐CRT, ≥1.0 or less); this difference was significant ( p < 0.05). Conclusions: We found that cutoff values for dose volume parameter ratios significantly predict grade 2 or greater RP. We believe that these parameter ratios could be useful in assisting evaluation of achievement degree of lung dose optimization in IMRT for LA‐NSCLC. Abstract : Incidence of grade 2 or greater pneumonitis between two groups divided by MLDIMRT/MLD3D‐CRT ≥1.0 or less.